KOMUNIKASI PUSTAKAWAN - khatibah khatibah (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2014)
Communication is the role of communication sciences to the library, any institutions  has a close relationship with communication including the library.An institution is difficult to develop and progress without communication,especially librarians who have a duty as an exellent service to users. If the library has the expertise and proficient in communicating, then there will be positive image  to users, so users have a positive attitude to the library